Building Structure Performance Analysis With and Without Shear Walls: Using Pushover Analysis - Nugraha, Cokorda Gede Eka; Sinarta, I Nengah; Aryastana, Putu (Fakultas Teknik Universitas Brawijaya, 2025)
The performance-based concept for earthquake-resistant buildings must be considered in the structural design of buildings. This concept analyzes the structural components to observe how the structure behaves during an earthquake, ensuring the building can withstand it safely. This study used pushover analysis to compare the performance of buildings with and without shear walls. The building's structure was constructed using three different types of modeling. The results showed that type 1 buildings have greater displacement and story drift values than type 2 and type 3. This finding suggests that type 2 and type 3 buildings had better structural rigidity than type 1. The plastic hinge mechanism in type 1 buildings refers to the SCWB design concept, where the plastic hinge mechanism occurs on the beam, whereas in type 2 and type 3 buildings, the plastic hinge machinery occurs in the shear wall area. Performance levels in types 1, 2, and 3, which use the FEMA 356 method, are at the immediate occupancy performance level.